Principles and applications of electrical engineering - Rizzoni, Giorgio; Kearns, James (McGraw Hill Education, 2016)
Offers an overview of electrical engineering discipline that is especially geared toward the many non-electrical engineering students who take this course. This title makes liberal use of practical applications to illustrate important principles.